PENULISAN SINGKATAN DALAM BAHASA SHORT MESSAGE SERVICE(SMS) STUDI KASUS DI STAIN JURAI SIWO METRO - Yawisah, Umi (Pusat Penelitian dan Pengabdian Masyarakat (P3M) STAIN Jurai Siwo Metro, 2015)
ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â Â In recent years people are enabled to communicate each other more easily by using cellular phone. One of the fitures in cellular phones is Short Message Service (SMS). It is also used in State Islamic College (STAIN Jurai Siwo Metro) between students and their lecturers. The problems arise when the students send SMS by using acronyms and unfamiliar abbreviations which is hard to be understood by their lecturers immediately, for instance sorbarbal, k2, s7, t4, rules/ rulez. The purpose of the study is to describe many kinds of abbreviation in SMS and to find out the specific types of SMS sent by the students to the lecturers of STAIN Jurai Siwo Metro. This is a qualitative study whose data are SMS languages sentÂ by the students to their lecturers from the same campus (STAIN Jurai Siwo Metro) from July to September 2014. Data from the writerâs cellular phone and other lecturersâ are written and classified in the data cards, then analysed by using contextual method. Those are done to know the incompleteness of the lexicon in SMS language because of the incomplete writing, the use of symbols of letters, and also acronyms. The last step is data analysis which is done descriptively. Based on the data analysis it is concluded that SMS languages sent by the students to their lecturers include the missing of vocal and also consonant, the missing of front and also back vowels, monophthongisation, number homophones, letter homophones, and acronyms. Â Keywords: SMS languages, vocal, consonant, acronym.Â